PENGARUH AKUNTANSI FORENSIK DAN PROFESSIONAL SKEPTICISM DALAM PENCEGAHAN FRAUD STUDI KASUS PADA AUDITOR PERWAKILAN BPKP PROVINSI BALI - I Gede Putu Tantra Suyasa; I Wayan Sudiana (UNHI Press, 2020)
Fraud is axproblem that often occurs in public financial management, and this causes a weakening of the social and economic aspects of a country. Thisx study aims to determine the effect of forensic accounting and Professional Skepticism in fraud prevention, Case Study at BPKP Bali Province. The population in this study were all BPKP employees of the Province of Bali, while the object of thex study (sample) was as many as 64 people. Thex technique of determining the sample was using the purposive sampling method. The results showed that forensic accounting variables, and the application of Professional Skepticism were both positive and significant influences on fraud prevention.